Macrobrachium indianum (Decapoda: Palaemonidae), a new species of hill stream prawn from Pambar River, Kerala, India - Pillai, P. M.; Unnikrishnan, V.; Prasannan, K. (Zootaxa, 2015)
Macrobrachium indianum new species is described from the Pambar River, Kerala, S. India. The species shares certain characters with M. gurudeve Jayachandran & Raji, 2004, M. bombayense Almelker & Sankolli, 2006 and M. kulkarnii Almelker & Sankolli, 2006, while it differs remarkably from these three species in distinctive diagnostic characters: rostral formula 7–8/3–4 with 1 postorbital teeth, one tooth above orbit; carapace smooth with distal end of rostrum directed downwards; cephalothorax longer than rostrum; in second chelate leg, proximal cutting edge of movable finger with two weak denticles, one weak denticle in immovable finger, carpus longer than merus, merus shorter than propodus and longer than ischium; dactylus the shortest podomere. Five thick and a few thin reddish brown bands of chromatophores are seen on carapace. Pigmentation is found mid and ventro-laterally on abdominal segments, pereiopods have chromatophores at the distal part of podomeres.